Feature Extraction for Face Recognition Using Haar Cascade Classifier (Future Science, 2021)
This is an era where sophisticated technology can develop rapidly, one of which is technology in the field of computer vision, such as facial recognition systems that can be used in security systems, access control systems, smart cards, and surveillance systems. In developing a face recognition system, the level of recognition accuracy can be influenced by several factors, namely lighting factors, facial expressions, facial positions, and changes in facial attributes. This study uses the Haar Cascade Classifier method in facial extraction and is assisted by using CNN for facial classification. This research uses python programming and the Open CV library.